EFEKTIVITAS PEMBELAJARAN KETERAMPILAN PROSES SAINS (KPS) PADA POKOK BAHASAN TERMO KIMIA DALAM MENINGKATKAN KEMAMPUAN SISWA DI SMA NEGERI 1 KRUENG BARONA JAYA KABUPATEN ACEH BESAR DINAS PENDIDIKAN ACEH - Muhammad Daud (UIN AR-RANIRY, 2018)
The effectiveness of learning Science Process Skills (SPS) on Thermochemistry subject is one of the factors that affecting the quality of learning. The aim of this study was to find out how is the planning, implementation, and evaluation of learning conducted by teachers in SMA Negeri 1 Krueng Barona Jaya of Aceh Besar. This research used descriptive qualitative approach. Technique of data collection is done through observation, interview, and documentation study. The data analysis procedure is done through data reduction, data display, and verification. The subjects of this study were principals, vice principals, chemistry subject teachers, and students. The results showed that: (1) The Learning Science Process Skills (SPS) planning that conducted by the teachers was done with the preparation of the Lesson Plans, Learning activities that followed by a syllabus development procedure based on competency standards and basic competencies; (2) The process of implementation of learning Skills Process of Science (SPS) was done gradually by using the implementation plan of learning. In the initial stages, the core stage, and at the closing stage the teacher gave students the opportunity to write down the material presented; and (3) the evaluation of learning programs that conducted by the teachers in the written test form and includes three stages of assessment: daily test, mid-semester test, and semester re-examination.